Ideologi Budaya Populer dalam Sinetron Sitti Nurbaya Versi TVRI dan Trans TV - Suaka, I Nyoman (Mudra Jurnal Seni Budaya, 2013)
The Sitti Nurbaya research on the TV-series form is due to under consideration that, this show is to be very fond of Indonesian society. The director and the producer of this series obtained compliments and scorn, even just in order to be challenged by a group of audience. Another audience threatened in order to stop the Sitti Nurbaya series show because it is considered to be able to bring down the Minangkabau people's prestige. The problem of the research is what kind of ideology does support the show of TVRI an Trans TV-version of Sitti Nurbaya's series considered to the popular culture perspective? The type of the research is qualitative one with the primary data source represents the DVD and VCD's TVRI and Trans TV-version of Sitti Nurbaya series. The theory which is used in this research is popular culture. The destructive sign system transposition such as, distortion and deconstruction, in large of number can be found in Sitti Nurbaya TV-series Trans TV show. The form which is evaluated as the appreciative part is, the story is returned to its context. The television media capitalism strength adapted-Sitti Nurbaya novel as literature text-into TV-series form through text transposition i.e. crossing, destructing, erasing, humiliating, and protesting reference text politically.